Tribo-dynamic analysis for aero ball bearing with 3D measured surface roughness. (January 2022) - Shi, Xiujiang; Lu, Xiqun; Feng, Yan; Qiu, Zhuoyi
Highlights: A tribo-dynamic analysis procedure is developed for the predictions of the aero ball bearing with 3D measured roughness. The influences of structure parameters and running conditions on the bearing dynamic performance have been discussed. The roughness effects on lubrication state and friction-temperature of the aero ball bearing are investigated. The 3D dynamic subsurface stress of the aero ball bearing has been researched. Abstract: Tribological failures, like wear, scuffing and pitting, etc, often occur in aero ball bearings due to large dry contact area, high friction-flash temperature and stress concentration at the interface between the contacting ball and race. In this paper, a numerical tribo-dynamic analysis procedure is developed for the predictions of dynamic performance, lubrication state, friction-temperature, and subsurface stress of the aero ball bearing with 3D measured roughness. The numerical model is verified by comparing the friction coefficients with the testing results, which show well agreements and proves the presented model is available. The dynamic performance of bearing at different azimuth angle are studied, which indicate the increasing radial load and speed result in more asymmetric distributions of the contact load, stress and slide-roll ratio, the maximum values and the unloaded-region become larger. With the increase of the inner race groove coefficient and the contact angle, the pv value and the radial stiffness decrease clearly. The tribology behaviors of the ball bearing are also investigated, the obtained results indicate that the heavy-load and low-speed lead to large dry contact areas, high friction-temperature, and high local stress peaks, the lubrication state become worse, which may further cause the failures of mass wear, scuffing and micro-pitting.